Minimally Invasive Surgery Oblique Lumbar Interbody Debridement and Fusion for the Treatment of Lumbar Spondylodiscitis. Issue 4 (10th June 2020) - Wang, Bingjin; Chen, Chao; Hua, Wenbin; Ke, Wencan; Lu, Saideng; Zhang, Yukun; Zeng, Xianlin; Yang, Cao
Abstract : Objective: To evaluate the efficacy and feasibility of minimally invasive oblique lumbar interbody debridement and fusion for the treatment of conservatively ineffective lumbar spondylodiscitis. Methods: This is a retrospective study. Between December 2016 and November 2017, a total of 14 consecutive patients (eight males and six females, with an average age of 49.1 years, range from 42 to 74 years) with single‐level lumbar spondylodiscitis were included in the study. The inclusion criteria include single‐level spondylodiscitis without spinal deformity or epidural abscess, ineffective conservative treatment (continuously aggravated clinical symptoms and uncontrollable infective symptoms treated with antibiotics for more than 6 weeks), minimally invasive oblique lumbar interbody fusion surgery (Mis‐OLIF) and iliac graft for the treatment of lumbar spondylodiscitis, and postoperative follow‐up >12 months. Each patient was treated Mis‐OLIF. Clinical outcomes including demographic characteristics, erythrocyte sedimentation rate (ESR), C‐reactive protein (CRP), visual analog scale (VAS), the Oswestry Disability Index (ODI), American Spinal Injury Association neurological classification, and lordotic angle were analyzed. Results: The infectious levels included L1/2 (one patient), L2/3 (two patients), L3/4 (eight patients), and L4/5 (three patients). The pathogens found in these patients included Staphylococcus aureus (5), brucellosis (6), and enterobacterium (2). The pathogen was undefined in one patient. The mean duration of the surgery, mean blood loss, and mean follow‐up were 89.3 ± 17.5 min, 155.0 ± 49.4 mL, and 16.8 ± 4.2 months, respectively. The ESR and CRP decreased after Mis‐OLIF and antibiotic administration. The average preoperative VAS score was 6.9 ± 0.9, then decreased to 3.0 ± 1.0 (t = 14.18, P  < 0.001) and 0.6 ± 0.7 (t = 20.68, P  < 0.001) before discharge and at final follow‐up, respectively. The average preoperative ODI score was 58.4 ± 13.0, then decreased to 28.3 ± 6.1 (t = 18.6, P  < 0.001) and 8.0 ± 4.6 (t = 22.7, P  < 0.001) before discharge and at final follow‐up, respectively. None of the patients developed postoperative ileus, vascular injury, nerve injury, and ureteral injury. One patient suffered incision‐related complication that healed by debridement and dressing change. One patient developed subsidence of autologous iliac bone before discharge and achieved complete bony fusion after staying in bed and fixing it with a brace at 3 months follow‐up. All patients achieved bony fusion at final follow‐up. Conclusion: Mis‐OLIF without anterior or posterior instrumentation and iliac graft is an effective and viable approach for the treatment of conservatively ineffective lumbar spondylodiscitis without spinal deformity or epidural abscess.